2013
DOI: 10.1097/ccm.0b013e318275871a
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in the Critically Ill

Abstract: The specific toxic effect of monomeric nonionic low-osmolar iodinated contrast medium in ICU patients with multiple renal aggressions seemed minimal. Severity of disease and the global nephrotoxic burden were risk factors for acute kidney injury, regardless of iodinated contrast medium infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 30 publications
6
23
0
Order By: Relevance
“…Our findings corroborate prior propensity score studies that also found similar rates of AKI, emergent dialysis, and short-term mortality between contrast-enhanced and unenhanced CT scan recipients, even in patients with renal insufficiency 7,10,11,19 . Our current study builds upon these findings in multiple ways.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings corroborate prior propensity score studies that also found similar rates of AKI, emergent dialysis, and short-term mortality between contrast-enhanced and unenhanced CT scan recipients, even in patients with renal insufficiency 7,10,11,19 . Our current study builds upon these findings in multiple ways.…”
Section: Discussionsupporting
confidence: 90%
“…Arguably, the cardiac catheterization could have been delayed for several weeks, as necessary, following the first exposure during the iodinated CAT scan examination to avoid this double contrast exposure that arguably led to the precipitation of her dialysis-requiring AKI. Although, there is some doubt suggested in the literature whether contrast-induced nephropathy is a significant contributor to hospital-acquired AKI (17,18), the overriding evidence supports such a role, more so with repeated exposure and/ or intra-arterial iodinated contrast as occurs during cardiac catheterization (19)(20)(21). Case III: The 46-year old morbidly obese hypertensive Caucasian male inpatient, stage II CKD, baseline serum creatinine of 1.21 mg/dL eGFR 70 mL/min/1.73 m 2 BSA had a relatively low susceptibility to renal injury at the time of the elective procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Three among them [20,21,41] used propensity matching methods guaranteeing that the group exposed to IV contrast material and unexposed group had similar baseline characteristics and had a same likelihood of being exposed to IV contrast material. Moreover, two studies [20,21] among the three that used propensity matching methods used data collected over 10 years (from 2000 to 2010) and recruited 41,614 patients.…”
Section: Discussionmentioning
confidence: 99%